Hericium erinaceus enhances neurotrophic factors and prevents cochlear cell apoptosis in senescence accelerated mice. (March 2020) - Hwang, Juen-Haur; Chen, Chin-Chu; Lee, Li-Ya; Chiang, Hung-Te; Wang, Ming-Fu; Chan, Yin-Ching
Graphical abstract: Highlights: Hericium erinaceus prevents hearing degeneration in SAMP8 mice. Hericium erinaceus increases nerve growth factor expression. Hericium erinaceus prevents outer hair cell loss in the cochlea. Hericium erinaceus reduces caspase-independent apoptosis. Abstract: This study aimed to investigate the effects of Hericium erinaceus (HE) on auditory function. Twenty-four 9-month-old male senescence-accelerated prone 8 (SAMP8) mice were randomly and equally assigned to the control group (group A) and two groups supplemented with 215.25 (group B) or 430.5 mg/kg BW of HE (group C) for 12 weeks. Compared with group A, group C had significantly smaller threshold shifts by auditory brainstem responses at the end of study. HE increased nerve growth factor (NGF) expressions in the spiral ganglion neurons (SGNs) and the temporal lobes, and also prevented outer hair cells (OHCs) loss in the middle turn of cochlea. In addition, group C had significantly lower apoptosis-inducing factor and poly (ADP-ribose) polymerase-1 expressions in the middle turn of cochlea, brainstem and temporal lobes. In conclusions, HE could prevent hearing degeneration possibly by increasing neurotrophic expression, preventing OHCs loss, and reducing the caspase-independent apoptosis signalings.